Erosion in Buenos Aires province: Coastal-management policy revisited - Isla, Federico Ignacio (2018)
As the Buenos Aires Province coastline is dominated by a longshore transport from south to north, obstructions performed at the beginning of the 20th century originated the width reduction of some beaches. Fields of groins were constructed without a master plan; therefore, more obstructions caused a dramatic decrease in the longshore sand supply. These defense alternatives were only applied in the counties of the southeast of the province (General Pueyrredon, General Alvarado, Mar Chiquita), close to the quarries, and with resistant abrasion platforms. Northern beaches (Villa Gesell, Pinamar and Partido de la Costa), on the other hand, are natural with a dissipative morphodynamics. Where the coastal route is close to active cliffs, riprap structures were constructed parallel to the coastline. Today, the southeastern coast remains with the higher erosion rates of the Buenos Aires coastline. With the aim of aerial and satellite photographs, and images, erosion rates were calculated. In order to analyze the success of coastal defenses, comparisons were established according to two intervals: 1960–1980, and 1980–2008. Defense structures have contributed to the decrease in the erosion rates in some areas; in other areas, the rates have increased due to the drift obstruction. In some critic areas, and considering present erosion rates, future positions of the coastline were simulated for the next 20–30 years. At the same time, there are new unexpected problems derived from a project to construct detached breakwaters that were not completed, and considering jetties that were constructed without a previous impact-assessment analysis.